2020
DOI: 10.1021/jacs.0c07956
|View full text |Cite
|
Sign up to set email alerts
|

Feeding a Molecular Squid: A Pliable Nanocarbon Receptor for Electron-Poor Aromatics

Abstract: A hybrid nanocarbon receptor consisting of a calix[4]arene and a bent oligophenylene loop (“molecular squid”), was obtained in an efficient, scalable synthesis. The system contains an electron-rich cavity with an adaptable shape, which can serve as a host for electron deficient guests, such as diquat, 10-methylacridinium, and anthraquinone. The new receptor forms inclusion complexes in the solid state and in solution, showing a dependence of the observed binding strength on the shape of the guest species and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 112 publications
0
17
0
4
Order By: Relevance
“…This color change was the result of the increased charge transfer from the phenolate to the acridinium moiety in 36 2 + (Figure 13b). Upon changing the cation of the base to less coordinating ions (Na + , K + , (CH 3 CH 2 ) 4 N + , Cs + ), a change of the spectral properties was observed with the appearance of a new species (λ max = 490 nm) attributed to the quinoid form (37). In all cases, slow conversion of the quinoidic calix [4]arene to the corresponding bis-acridane receptor (35) was achieved (λ max = nm).…”
Section: Acridinium Appended To Calix[n]arenesmentioning
confidence: 99%
See 3 more Smart Citations
“…This color change was the result of the increased charge transfer from the phenolate to the acridinium moiety in 36 2 + (Figure 13b). Upon changing the cation of the base to less coordinating ions (Na + , K + , (CH 3 CH 2 ) 4 N + , Cs + ), a change of the spectral properties was observed with the appearance of a new species (λ max = 490 nm) attributed to the quinoid form (37). In all cases, slow conversion of the quinoidic calix [4]arene to the corresponding bis-acridane receptor (35) was achieved (λ max = nm).…”
Section: Acridinium Appended To Calix[n]arenesmentioning
confidence: 99%
“…M. Stępień and coworkers have functionalized a calix[4]arene with a oligophenylene loop ( 27 ) which delimits a flexible cavity (Figure 10a) [37] . Followed by NMR experiments, titration studies in CD 2 Cl 2 revealed a 1 : 1 host‐guest complex between Ac + and the oligophenylene loop through π‐π interactions (log K =3.77, Figure 10b).…”
Section: Acridiniums As Molecular Guestmentioning
confidence: 99%
See 2 more Smart Citations
“…Die Einbindung solcher Fragmente ermöglicht Untersuchungen neuer Funktionalitäten und optoelektronischer Eigenschaften dieser makrozyklischen Substanzklasse [13–17] . Zudem konnten durch diese methodischen Arbeiten neue geometrische Formen vom Makrozyklus bis hin zum molekularen Käfig erschlossen werden [18–21] . Während poröse molekulare Käfige intrinsisch ein Gastbindungsverhalten aufweisen, sind CPPs und verwandte gespannte Kohlenstoffmakrozyklen nur moderate supramolekulare Wirte, die sich meist auf die Bindung von Fulleren‐Gästen beschränken [22–27] .…”
Section: Figureunclassified